GRADASI Innovation Community Service (Exclusive Breastfeeding Awareness) in Pakuhaji Village Tangerang Regency - Silawati , Vivi; Lestari, Hartuti Puji; Palupi, Primarti Endang; Harida, Yuli; Yulyani; Masliyah; Purbasari (International Journal of Community Services, 2023)
Background: In the profile of the Pakuhaji Health Center in 2022, there were 3 major problems that occurred, seen from the K1 data for pregnant women, the target was 354 until March 2023, 312 achievements, from this data there is a gap of 11%. In childbirth assisted by health workers, the number of deliveries was 326, with 316 achieved up to March, from this data there was a gap of 14%. In newborns, the number of babies who underwent IMD was 244, 102 babies who received exclusive breastfeeding, from these adta there was a gap of 41.6%. Out of the three problems mentioned above, we conclude that the priority problem is the low coverage of exclusive breastfeeding. Objective: Carry out community service by carrying out activities ranging from collecting secondary data to conducting interventions and evaluating field activities. Methodology: The method used starts from situation analysis, continues with problem identification, and determines problem priorities. Then develop research instruments, surveys/research on problem determinants and collection of health databases, as well as conduct outreach. Results: Community midwifery practice carried out at BPM Hj. Yulyani, Pakuhaji, Tangerang Regency which was held at RT 02 RW 02 Kp. Rawakalong, Pakuhaji District, Tangerang Regency, has been carried out in the following stages: Regional Orientation, Self-Introduction Survey, Focus Group Discussion (FGD), Preparation of Planning of Action (POA), Intervention activities in the form of exclusive breastfeeding counseling to breastfeeding mothers and provision of snacks with GRADASI innovation (Exclusive Breastfeeding Awareness Movement), and ended with Evaluation and Closing. Conclusion: GRADASI activity is a combination of counseling and education activities about breastfeeding, complementary care practices in the form of Oxytocin massage and breast care in preparation for breastfeeding as well as the introduction of additional food for BOOSTER ASI made from Moringa Leaves. Hopefully the innovations we make can benefit the community.